The Relation Between Consumers' Frontal Alpha Asymmetry, Attitude, and Investment Decision - Di Gruttola, Francesco; Malizia, Andrea P.; D'Arcangelo, Sonia; Lattanzi, Nicola; Ricciardi, Emiliano; Orfei, Maria Donata (Frontiers in Neuroscience, 2021)
The frontal alpha asymmetry (FAA) is a neurophysiological measure of motivation and preference. Despite the FAA is associated to commercial pleasantness, conflicting evidence emerged in the literature regarding its relationship with behaviour. To study the association between FAA and consumers’ decision, we manipulated a commercial script to elicit diverse consumers’ attitudes and decisions, and to evaluate whether the FAA score is associated to their final investment. A little informative script (S1) was used to polarize consumers’ attitudes and investments towards unfavourable scores, while a more personalized message (S2) to elicit in customers a favourable attitude and higher investments. Twenty-one participants listened to the scripts and their FAA, attitude and monetary investment were measured. In S1, the FAA did not correlate with neither attitude nor the investment decision, while a robust negative correlation between these variables was found in S2. No other peripheral body and neural measures associated with attitude or final decision. Our data suggest that the FAA correlates with attitude and decision, when a commercial script is customized and provides an adequate information, likely leading the consumer to a more reasoned and planned decision-making process. When facilitating a favourable attitude towards an offer, the negative correlation of FAA and behaviour may reflect the involvement of a control system, whose role is to monitor and govern possible conflicts between approach and avoidance motivations. This observation provides additional indication on the value of FAA as a marker of consumer behaviours, and how it could be affected by experimental and contextual bias.